DNA Adducts Formed by Aristolochic Acid Are Unique Biomarkers of Exposure and Explain the Initiation Phase of Upper Urothelial Cancer - Stiborová, Marie; Arlt, Volker M; Schmeiser, Heinz H (International journal of molecular sciences, 2017)
Aristolochic acid (AA) is a plant alkaloid that causes aristolochic acid nephropathy (AAN) and Balkan endemic nephropathy (BEN), unique renal diseases frequently associated with upper urothelial cancer (UUC). This review summarizes the significance of AA-derived DNA adducts in the aetiology of UUC leading to specific A:T to T:A transversion mutations (mutational signature) in AAN/BEN-associated tumours, which are otherwise rare in individuals with UCC not exposed to AA. Therefore, such DNA damage produced by AA-DNA adducts is one rare example of the direct association of exposure and cancer development (UUC) in humans, confirming that the covalent binding of carcinogens to DNA is causally related to tumourigenesis. Although aristolochic acid I (AAI), the major component of the natural plant extract AA, might directly cause interstitial nephropathy, enzymatic activation of AAI to reactive intermediates capable of binding to DNA is a necessary step leading to the formation of AA-DNA adducts and subsequently AA-induced malignant transformation. Therefore, AA-DNA adducts can not only be utilized as biomarkers for the assessment of AA exposure and markers of AA-induced UUC, but also be used for the mechanistic evaluation of its enzymatic activation and detoxification. Differences in AA metabolism might be one of the reasons for an individual's susceptibility in the multi-step process of AA carcinogenesis and studying associations between activities and/or polymorphisms of the enzymes metabolising AA is an important determinant to identify individuals having a high risk of developing AA-mediated UUC.
Keywords: aristolochic acid; Humans; DNA adduct formation; urologické nádory; mutagenesis; Aristolochic Acids; lidé; Biomarkers; zvířata; nádorová transformace buněk; Disease Susceptibility; náchylnost k nemoci; Urologic Neoplasms; biologické markery; Balkan Nephropathy; carcinogenicity; Carcinogens; karcinogeny; Cell Transformation, Neoplastic; kyseliny aristolochové; Animals; adukty DNA; DNA Adducts; balkánská nefropatie; nephrotoxicity